Expansion of the Sphere of Social Insurance for Self-Employed Citizens in the BRICS Countries (on the Example of Brazil) - A. V. Burlak (Сибирское юридическое обозрение, 2018)
The article analyzes the change in the social insurance system for self-employed Brazilian citizens, thanks to two programs introduced in the 2000s, which showed a high result in terms of legalization and inclusion in the social security system of such employees. The self-employed Brazilians are, to a large extent, excluded from the national social insurance system. The programs provide an opportunity for micro-entrepreneurs and the selfemployed to simplify administrative procedures and adapt the level of social insurance contributions to their incomes. The data presented by the Author illustrates the effectiveness of programs that can also be implemented in other countries that are part of the BRICS organization.